Current State Of Research About De Chagas Disease In Peru - Cornejo Donayre, Alberto (1967)
In 1919 the first case of Chagas disease in Peru ( 1) was diagnosed , but two years earlier had shown infection with T. cruzi in triatomideos captured in a valley of the department of Arequipa (2 ) . Subsequently no investigation was carried out on this disease until 1943-1944 ( 3) , the first epidemiological studies were made, the second case diagnosed and showing natural infection with T. cruzi in guinea pigs and dogs in a zone where we now know that disease is endemic. It is from 1950-51 (4) (5) , that research and report that we had the opportunity to present the VI International Congress of Tropical Medicine and Malaria (6 ) will intensify, we collect 204 cases diagnosed by several researchers in polls made in 7 departments and the first came from Madre de Dios ( Arequipa , Tacna , Moquegua , San Martín , Cajamarca and Amazonas) ; plus information on triatomideos , animal reservoirs of T. cruzi and other important aspects of this epidemic logical Trypanosomiasis in those departments and Tumbes , Piura, La Libertad, Lima , Junín , read and Cuzco .